First, Do No Harm: From Diversity and Inclusion to Equity and Anti-racism in Interpersonal Violence Research and Scholarship - Tajima, Emiko A. (Journal of interpersonal violence, 2021)
This article aims to support interpersonal violence (IPV) researchers in promoting diversity and inclusion in their research and scholarship and urges the IPV field to advance a racial equity, anti-oppressive, and justice-driven research agenda. The article discusses a range of factors to consider at each stage of the research process as researchers seek to be inclusive, responsive to diversity concerns, and seek equity. The researcher’s perspective and positionality are discussed and the importance of critical self-examination of one’s position in relation to the research is emphasized. Participatory and collaborative research processes are recommended, to engage with community partners, strengthen the validity of the findings, and help ensure that the research benefits the participants. Examples illustrate ways researchers might support diversity and inclusion with respect to sampling and measurement, cultural validity, and the conceptualization and operationalization of race. Recommendations are offered to promote diversity, equity, and inclusion when analyzing data, interpreting results, and writing up the study. The importance of a strengths-based approach and structural level analysis is emphasized. This article goes beyond discussion of the minimum, “do no harm” standard that researchers should meet in attending to diversity and inclusion in research and urges the pursuit of equity, anti-racism, and justice toward dismantling those structures that perpetuate violence in its many forms. Researchers are encouraged to ask themselves: Where would I situate my research? Is it racist, not racist, or anti-racist? Not all IPV research has the goal of dismantling inequities, but we should aspire that it do so.